2021
DOI: 10.3389/fpsyg.2021.616812
|View full text |Cite
|
Sign up to set email alerts
|

On the Multimodal Path to Language: The Relationship Between Rhythmic Movements and Deictic Gestures at the End of the First Year

Abstract: The aim of this study is to analyze the relationship between rhythmic movements and deictic gestures at the end of the first year of life, and to focus on their unimodal or multimodal character. We hypothesize that multimodal rhythmic movement performed with an object in the hand can facilitate the transition to the first deictic gestures. Twenty-three children were observed at 9 and 12 months of age in a naturalistic play situation with their mother or father. Results showed that rhythmic movements with objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Interestingly, it has been shown that when infants nine months of age vocalize while rhythmically moving their limbs, caretakers are more likely to respond as opposed to when the infant moves without vocalization (Moreno-Núñez et al, 2021). When 9-month old infants are more frequently rhythmically moving and vocalizing at the same time, this positively relates to their use of showing-and attention-grabbing deictic gestures at 12 months of age (Murillo et al, 2021). Thus vocal-motor babbling is possibly a biomechanical synchronization of vocalization with peripheral bodily states, thereby imbuing the utterances with a particularly potent communicative invitation to the parent.…”
Section: Ontogeny: Gesture-vocal Babbling As An Exploration Of Biomechanicsmentioning
confidence: 98%
See 1 more Smart Citation
“…Interestingly, it has been shown that when infants nine months of age vocalize while rhythmically moving their limbs, caretakers are more likely to respond as opposed to when the infant moves without vocalization (Moreno-Núñez et al, 2021). When 9-month old infants are more frequently rhythmically moving and vocalizing at the same time, this positively relates to their use of showing-and attention-grabbing deictic gestures at 12 months of age (Murillo et al, 2021). Thus vocal-motor babbling is possibly a biomechanical synchronization of vocalization with peripheral bodily states, thereby imbuing the utterances with a particularly potent communicative invitation to the parent.…”
Section: Ontogeny: Gesture-vocal Babbling As An Exploration Of Biomechanicsmentioning
confidence: 98%
“…Indeed, there hides an evolutionary logic in the idea that acoustics are informative about the peripheral body (Tchernichovski and Oller, 2016, p.422) such that "in addition to broadcasting respiratory events, the vocal apparatus could evolve the capacity to express respiratory pressure (via modulation of sound amplitude) or muscle tension (via modulation of pitch), and so on." The logic is that it can be adaptive for peripheral bodily conditions to imprint on the voice, for example, in the case where an infant is expressing their emotional-psychological well-being to the caretaker (Moreno-Núñez et al, 2021;Murillo et al, 2021;Mehr et al, 2021). Interestingly, it has been shown that when infants nine months of age vocalize while rhythmically moving their limbs, caretakers are more likely to respond as opposed to when the infant moves without vocalization (Moreno-Núñez et al, 2021).…”
Section: Ontogeny: Gesture-vocal Babbling As An Exploration Of Biomechanicsmentioning
confidence: 99%
“…Third, rhythmic arm movements are postulated to be the precursor of vocal-entangled gestures that accompany day-to-day adult communication (Pouw and Fuchs, 2022). As was shown in previous studies (Thelen, 1979;Locke et al, 1995;Ejiri, 1998;Ejiri and Masataka, 2001;Iverson and Fagan, 2004;Iverson and Wozniak, 2007;Burkhardt-Reed et al, 2021), rhythmic manual movements often co-occur with infants' vocalizations and this co-occurrence is observed at much earlier developmental stages than other types of gestures-such as pointing (emerging around 12 months of age; Colonnesi et al, 2010;Murillo et al, 2021) or iconic gestures (emerging around 26 months of age, Ozcaliskan and Goldin-Meadow, 2011). Thus, it seems that rhythmic arm movements that accompany vocal learning may serve as a precursor to the gesture-speech system (Iverson and Fagan, 2004;Pouw and Fuchs, 2022).…”
Section: Discussionmentioning
confidence: 78%
“…In contrast, an extended repertoire of signals may encompass other preverbal signals that have received growing interest in recently published articles as indicators of early pragmatic skills. For example, recent studies have begun to investigate proximal deictic gestures, in which a referent object remains in contact with the hand, for example, showing and giving gestures (Murillo et al, 2019), as a likely transition to distal deictic gestures (Liszkowski et al, 2006(Liszkowski et al, , 2008 that can even predict language skills at 18 months of age (Choi et al, 2021). The study of the pragmatic usage, that is, the use of a signal for its signal value, of gestural signals has extended to bodily gestures such as body or rhythmic movements.…”
Section: Introductionmentioning
confidence: 99%
“…Infants aged 11 to 16 months transition from the use of gestures to the use of spoken words to communicate with surrounding adults (Aureli et al., 2017; Bates et al., 1975; Igualada et al., 2015; Mccune & Zlatev, 2015; Murillo et al., 2021). Speech onset results in the coexistence of the two communication modalities, although the vocal modality progressively becomes prominent (Guidetti et al., 2014; Iverson & Goldin‐Meadow, 2005).…”
Section: Introductionmentioning
confidence: 99%